Clostridium Difficile-Associated Diarrhea in 200 Canadian Children - Véronique Morinville; Jane McDonald (Canadian Journal of Gastroenterology)
OBJECTIVE: Clostridium difficile-associated diarrhea is a major problem in adults. The present study was conducted to assess risk factors and outcomes in children with C difficile-associated diarrhea.